Woodrow Wilson and the roots of modern liberalism - Pestritto, Ronald J. (American intellectual culture., 2005)
Woodrow Wilson and the Roots of Modern Liberalism highlights Wilson's sharp departure from the traditional principles of American government, most notably the Constitution. Ronald J. Pestritto argues that Wilson's unfailing criticism places him clearly in line with the Progressives' assault on the original principles of American constitutionalism. Drawing primarily from early writings and speeches that Wilson made during his years as a scholar, Pestritto examines the future president's clear and consistent ideologies that laid the foundation for later actions taken as a public leader. --From publisher's description.